Geometry-induced enhancement factor improvement in covered-gold-nanorod-dimer antennas - Ramos, Iván A. (2021)
Illuminated gapped-gold-nanorod dimers hold surface plasmon polaritons (SPPs) that can be engineered, by an appropriate choice of geometrical parameters, to enhance the electromagnetic field at the gap, allowing applications in molecular detection via surface-enhanced Raman spectroscopy (SERS). Envisioning hybrid devices in which the SERS spectroscopy of molecules in the gap is complemented by electrical measurements, it arises the question of designing efficient geometries to contact the nanorods without decreasing the enhancement factor (EF) of the nanoantenna, i.e., the figure of merit for SERS spectroscopy. Within this framework we theoretically study the feasibility to fabricate designs based on covering with gold the far-from-the-gap areas of the dimer. We show that by tuning the geometrical parameters of the designs these systems can reach enhancement factors larger than the best achieved in the uncovered dimer: this supremacy survives even in the presence of dimer asymmetries and vacancies at the interfaces between the nanorods and the covering layers. Our results show that geometrical modifications away from the gap can improve the optical response at the gap, thus enabling the use of these devices both for hybrid and optical applications.